2021
DOI: 10.1016/j.seppur.2021.119358
|View full text |Cite
|
Sign up to set email alerts
|

Cytinus hypocistis (L.) L.: Optimised heat/ultrasound-assisted extraction of tannins by response surface methodology

Abstract: Tannins are a class of phenolic compounds commonly found in plants and studied for their bioactive and inhibitory enzyme properties. Cytinus hypocistis (L.) L. is a wild edible parasitic plant whose biological properties have been correlated with its high tannin content. Thus, studying the extraction of tannins from C. hypocistis will give comprehensive clues to enhance the recovery of these high added-value bioactive compounds. The present work applied Response Surface Methodology (RSM) to optimise tannins ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This shows that their response surface had a curvature, and the TTC value reached a maximum under the optimal conditions of the variables, and a further increase in the variables would decrease TTC values. A previous study of tannins obtained from Cytinus hypocistis (L.) via the UAE method reported that the highest TTC was obtained at a higher solvent concentration …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that their response surface had a curvature, and the TTC value reached a maximum under the optimal conditions of the variables, and a further increase in the variables would decrease TTC values. A previous study of tannins obtained from Cytinus hypocistis (L.) via the UAE method reported that the highest TTC was obtained at a higher solvent concentration …”
Section: Resultsmentioning
confidence: 99%
“…A previous study of tannins obtained from Cytinus hypocistis (L.) via the UAE method reported that the highest TTC was obtained at a higher solvent concentration. 24 2.1.5. Effect of Variables on Antioxidant Activity.…”
Section: Effect Of Variables On the Tpc The Secondary Polynomial Equa...mentioning
confidence: 99%
“…V. Silva et al, 2020;Silva et al, 2021a). Galloyl-bis-HHDP-glucose, for example, is always the major compound identified in the extract, but its extracted concentrations decreased from the sample harvested in 2018-2019 and 2020.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The extracts were prepared using Heat-Assisted Extraction (HAE) at the optimum global condition determined during previous work; the samples (0.8 g) were mixed with a hydroethanolic solution (40 mL; 95.1 min, 46.4 • C, and 74.3%). The mixture was extracted in a water bath, as previously described (Silva et al, 2021a). A total of five hydroethanolic extracts were prepared: the whole C. hypocistis (CH); parasited H. lasianthum aerial parts (PHLAP); parasited H. lasianthum roots (PHLR); non-parasited H. lasianthum aerial parts (HLAP); and non-parasited H. lasianthum aerial roots (HLR).…”
Section: Plant Materials and Extracts Preparationmentioning
confidence: 99%
See 1 more Smart Citation